Cleft Palate Induced by Mycophenolate Mofetil Is Associated with miR-4680-3p and let-7c-5p in Human Palate Cells - Hiroki Yoshioka; Hanane Horita; Yosuke Tsukiboshi; Hisaka Kurita; Aya Ogata; Kenichi Ogata (Non-Coding RNA)
Background/Objectives: Cleft palate is a birth defect associated with environmental and genetic factors. Disturbance of microRNAs (miRNAs) and exposure to medicinal agents during pregnancy can cause cleft palate. Although an association between medicine-induced cleft palate and miRNAs has been suggested, it remains to be fully elucidated. This study aimed to clarify the molecular mechanism underlying mycophenolate mofetil (MPM)-induced inhibition of cell proliferation and miRNA expression in human embryonic palatal mesenchymal (HEPM) cells. Methods: Cell viability, apoptosis, and cell cycle-related markers were evaluated 48 h after MPM treatment. In addition, miRNA levels and expression of their downstream genes were measured, and a rescue experiment was performed using miR-4680-3p and/or let-7c-5p inhibitors. Results: MPM dose-dependently reduced HEPM cell viability. Additionally, MPM treatment suppressed cyclin-D1, cyclin E1, cyclin-dependent kinase (CDK)-2, and CDK6 expression in HEPM cells. Furthermore, MPM upregulated miR-4680-3p and let-7c-5p expression and downregulated the downstream genes of each miRNA. Moreover, miR-4680-3p and/or let-7c-5p inhibitors alleviated MPM-induced inhibition of cell proliferation. Conclusions: These results suggest that MPM-induced cleft palate is associated with miR-4680-3p and let-7c-5p expression in HEPM cells.